1996
DOI: 10.1159/000147886
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Bridge Muscle on Left Anterior Descending Coronary Artery Differs from Subepicardial Myocardium of the Left Ventricle in Dogs

Abstract: The myocardial bridge (MB) is a muscle band found sporadically above the coronary artery (CA) in humans and certain animals such as the dog, cat and sheep. The purpose of our study was to compare the structure of the MB muscle with that of tissue from the subepicardial myocardium. The histological studies included toluidine blue staining of 1-µm-thick sections and Gomori’s trichrome staining of canine cardiac samples. The MB muscle of the dog heart is characterized by a distinctive spatial arrangement, with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…The most frequent position of MBs in regard to RIA of the LCA found in our study is similar to that reported by Yamaguchi et al, (1996) in dogs. It can be compared with the incidence of MBs reported in different species.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The most frequent position of MBs in regard to RIA of the LCA found in our study is similar to that reported by Yamaguchi et al, (1996) in dogs. It can be compared with the incidence of MBs reported in different species.…”
Section: Resultssupporting
confidence: 91%
“…The frequency of MB, their location, morphology and clinical significance arouse some controversies (Nikoli} and Teofilovski Parapid, 1995;Nikoli} et al, 1996;Mohlenkamp et al, 2002;Bharambe and Arole, 2008). The same thing is with the most of the fundamental questions based in relation to hearts muscle coverage of coronary arteries (Morales et al, 1993), as whether MBs are normal variants of the coronary arteries anatomy (Yamaguchi et al, 1996) or are an anomaly. Angelini et al (2002) proposed that a coronary artery anomaly should be defined as any coronary pattern with a morphological feature encountered in <1%.…”
Section: Introductionmentioning
confidence: 95%
“…The myocardial bridges (MB) are defined as a short segment of the superficial muscular bands that run across coronary arteries (CA) (1–4). Myocardial bridge is a muscle band found sporadically above the CA in both humans and certain animals such as the dog, cat, sheep, goat, chimpanzee and orangutan (5–10).…”
Section: Introductionmentioning
confidence: 99%
“…the coronary artery 21 , and with results reporting that the presence of the myocardial bridge may influence the arterial tissue through haemodynamic forces alterations through its contractions 5 . Therefore, the highest obliquity of fibers 3 , as well as the environment in which this artery is involved [21][22][23] could be a compensatory disposition…”
Section: Figure 4 -Photomicrography Of Intima Tunica Presenting the mentioning
confidence: 84%
“…Therefore, the highest obliquity of fibers 3 , as well as the environment in which this artery is involved [21][22][23] could be a compensatory disposition…”
Section: Figure 4 -Photomicrography Of Intima Tunica Presenting the mentioning
confidence: 99%